2015
DOI: 10.1007/s00421-015-3244-3
|View full text |Cite
|
Sign up to set email alerts
|

Avenanthramide supplementation attenuates eccentric exercise-inflicted blood inflammatory markers in women

Abstract: Our data of pre- and post-supplementation difference reflect an interaction between repeated measure effect of eccentric exercise and AVA in diet. Long-term AVA supplementation can attenuate blood inflammation markers, decrease ROS generation and NFkB activation, and increased antioxidant capacity during an eccentric exercise bout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 37 publications
4
26
0
1
Order By: Relevance
“…This study showed that IL-1β increased significantly in retinal capillary cells under hyperglycemic conditions ( Carmo et al, 2000 ; Kowluru and Odenbach, 2004b ). Interestingly, IL-1 activation can lead to release of more ROS and NF-κB translocation to the nucleus, thus creating a continuous inflammatory response ( Figure 1 ) ( Chang and LoCicero, 2004 ; Koenig et al, 2016 ). Further, IL-1β is associated with apoptosis of retinal capillary cells, probably via NF-κB and caspase-3 activation ( Kowluru and Odenbach, 2004a ; Gupta et al, 2017 ; Mendiola and Cardona, 2017 ).…”
Section: Perturbation Of the Redox System In Drmentioning
confidence: 99%
“…This study showed that IL-1β increased significantly in retinal capillary cells under hyperglycemic conditions ( Carmo et al, 2000 ; Kowluru and Odenbach, 2004b ). Interestingly, IL-1 activation can lead to release of more ROS and NF-κB translocation to the nucleus, thus creating a continuous inflammatory response ( Figure 1 ) ( Chang and LoCicero, 2004 ; Koenig et al, 2016 ). Further, IL-1β is associated with apoptosis of retinal capillary cells, probably via NF-κB and caspase-3 activation ( Kowluru and Odenbach, 2004a ; Gupta et al, 2017 ; Mendiola and Cardona, 2017 ).…”
Section: Perturbation Of the Redox System In Drmentioning
confidence: 99%
“…Avenanthramides (AVs), found exclusively in oats, are made up of an anthranilic acid derivate and a hydroxycinnamic acid derivate linked by a pseudo-peptide, (Collins 1989) and have anti-inflammatory effects (Koenig et al 2016). Koenig et al demonstrated that AV supplementation attenuates the eccentric exerciseinflicted blood inflammatory markers in women (Koenig et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A portion of 5B cookies provides 4.8 mg of AVNs, which is more than the double of the maximal daily AVN intake in oat consumers (Pridal et al ., ). The few data available on in vivo studies showed that the consumption of 9.2 mg day −1 AVNs are sufficient to provide effect on exercise induced inflammation (Koenig et al ., ). A double serving size (100 g) of 5B cookies, administered daily, reaches the above value, recognised to provide anti‐inflammatory activity.…”
Section: Resultsmentioning
confidence: 97%